2015
DOI: 10.1523/jneurosci.2690-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Arc-Expressing Neuronal Ensembles Supporting Pattern Separation Require Adrenergic Activity in Anterior Piriform Cortex: An Exploration of Neural Constraints on Learning

Abstract: Arc ensembles in adult rat olfactory bulb (OB) and anterior piriform cortex (PC) were assessed after discrimination training on highly similar odor pairs. Nonselective ␣-and ␤-adrenergic antagonists or saline were infused in the OB or anterior PC during training. OB adrenergic blockade slowed, but did not prevent, odor discrimination learning. After criterion performance, Arc ensembles in anterior piriform showed enhanced stability for the rewarded odor and pattern separation for the discriminated odors as des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…The effect of PCx 5-HT during associative learning is completely unexplored; however, optogenetic stimulation of 5-HT inputs decreases spontaneous PCx firing without affecting odor-evoked PCx activity (Lottem et al 2016), which could facilitate cortical olfactory learning and plasticity. Blockade of NE receptors in PCx prevents acquisition of olfactory associative appetitive learning in both pups (Ghosh et al 2015;Morrison et al 2013) and adults (Shakhawat et al 2015) and NE stimulation reverses learning-induced hyperexcitability of PCx pyramidal cells (Brosh et al 2006), indicating a function for NE in olfactory learninginduced PCx plasticity. Data from electrophysiological and computational studies indicate ACh places PCx in a permissive state for both learning and recall in adult associative learning (Barkai et al 1994; Barkai and Hasselmo 1997;Hasselmo et al 1992) by simultaneously suppressing synaptic transmission and enhancing synaptic modification (Linster and Hasselmo 2001) and enhancing long-term potentiation in PCx pyramidal cells (Hasselmo and Barkai 1995;Patil et al 1998).…”
Section: Piriform Cortexmentioning
confidence: 98%
“…The effect of PCx 5-HT during associative learning is completely unexplored; however, optogenetic stimulation of 5-HT inputs decreases spontaneous PCx firing without affecting odor-evoked PCx activity (Lottem et al 2016), which could facilitate cortical olfactory learning and plasticity. Blockade of NE receptors in PCx prevents acquisition of olfactory associative appetitive learning in both pups (Ghosh et al 2015;Morrison et al 2013) and adults (Shakhawat et al 2015) and NE stimulation reverses learning-induced hyperexcitability of PCx pyramidal cells (Brosh et al 2006), indicating a function for NE in olfactory learninginduced PCx plasticity. Data from electrophysiological and computational studies indicate ACh places PCx in a permissive state for both learning and recall in adult associative learning (Barkai et al 1994; Barkai and Hasselmo 1997;Hasselmo et al 1992) by simultaneously suppressing synaptic transmission and enhancing synaptic modification (Linster and Hasselmo 2001) and enhancing long-term potentiation in PCx pyramidal cells (Hasselmo and Barkai 1995;Patil et al 1998).…”
Section: Piriform Cortexmentioning
confidence: 98%
“…Storage of information is made possible by NMDA-dependent, associative plasticity of connections [13][14][15]. Furthermore, changes in piriform network activity [16][17][18] and stabilization of odor representations [19] have been observed after associative olfactory learning. Finally, excitotoxic lesions of the posterior PCx in rats perturb odor fear memories [20], and optogenetic stimulation of artificial piriform ensembles is sufficient to drive learned behaviors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Local field potential (LFP) oscillations in the olfactory bulb (OB) reflect circuit processing for stimulus detection and sensory decision making for animals learning to differentiate between odorants (Kay, 2014 ; Frederick et al, 2016 ). Local infusion of noradrenergic drugs has shown that noradrenergic modulation plays a role in olfactory bulb/piriform cortex circuit processing for successful odorant discrimination by altering mitral/tufted cell synchronized firing, signal to noise ratio in the output to piriform cortex and pattern separation in piriform cortex (Doucette et al, 2007 , 2011 ; Escanilla et al, 2012 ; de Almeida et al, 2015 ; Shakhawat et al, 2015 ). In addition, studies of circuit dynamics in olfactory bulb slices indicate that adrenergic receptor activation leads to long term enhancement of synchronized oscillations in the olfactory bulb (Pandipati et al, 2010 ), and infusion of the beta noradrenergic blocker propranolol alters the odorant-elicited oscillatory response in the olfactory bulb for the rewarded odorant (Gray et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%